Implementation And Strengthening Oversight Function In The DPRD of Gorontalo Province - Abdul Hamid Tome; Supriyadi A. Arief (Journal of Law and Policy Transformation, 2024)
The oversight function is one of the functions of the DPRD, but it has not worked well in practice. Therefore, through this research, we are trying to generate ideas regarding implementing the DPRD's oversight function on regional government administration, mainly carried out by the Gorontalo Province DPRD. This research is empirical legal research because it examines problems in the legal field, namely in the Gorontalo provincial DPRD as the research object. This qualitative research approach is a way of analyzing research results that produce descriptive data. This research concludes that the form of implementation of the oversight function carried out by the Gorontalo Province DPRD is in two forms, namely: supervision in hearings by inviting stakeholders and direct visits, both planned and unannounced (sudden inspections), as well as supervising the implementation of follow-up actions—results of examination of financial reports by the Financial Audit Agency. Therefore, the implementation of the oversight function carried out by the Gorontalo Provincial DPRD can be improved through the use of social media in receiving reports from the public so that it will make it easier for the monitoring mechanism by the Gorontalo Provincial DPRD as well as to control budget availability in the implementation of regional regulations so that budget allocation for the implementation of regional rules is appropriate. It has been established and can be used efficiently and accountably.